Quantum Therapy: A New Way in Osteoporosis Primary Prevention and Treatment - Stagnaro, Sergio; Caramel, Simone (Journal of Pharmacy and Nutrition Sciences, 2012)
The paper highlights the role played by quantum therapy in Osteoporosis Primary Prevention and treatment. We provide an overview of other useful treatments in Osteoporosis prevention such as CoQ10, Melatonin and Mediterranean Diet comparing their efficacy to that offered by the quantum therapy. This is done through ‘Quantum Biophysical Semeiotics’ bed-side evaluation, monitoring the results and efficiency of ongoing therapies aimed at improving mitochondrial and endothelial function, when it is unpaired in any biological systems. 'Quantum Biophysical Semeiotics’ theory is an extension of medical semeiotics. It is grounded on a multidisciplinary approach that involves chemistry and biology, genetics and neuroscience, chaos theory and quantum physics. It is based on the method of ‘Auscultatory Percussion’, through which by means of the common stethoscope, it is possible to listen to the signs that the body gives us when appropriately stimulated. The stimuli are used to induce consistent behaviour -typical of dissipative systems far from equilibrium, according to Prigogine - in precise and well defined biological systems of the human body, thus giving local qualitative information on the state of health or disease, whether potential, being developed but not yet evident by usual clinical trial, effective or even in chronic phase. The 'Quantum Biophysical Semeiotics’ theory provides very detailed case studies based on the latency time, duration, and intensity of the reflexes, which play a central role in such a diagnostic method.